2021
DOI: 10.1002/adts.202100128
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Potential Sources in Infinite 2D Arrays: Diffusion through Composite Membranes, Micro‐Electrochemistry, Entrance Resistance, and Other Examples

Abstract: Regular 2D arrays of potential sources on impervious “screens” are a mathematical idealization for the description of a number of natural and/or technological processes. At steady state, they are described by Laplace equation with suitable boundary conditions. This study explains the evolution of boundary conditions from a given potential to a given potential gradient at infinity with increasing size of arrays and provides a criterion for micro‐ and macro‐arrays in terms of distance to potential‐defining surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Understanding the transport phenomena of a single or isolated nanochannel is of fundamental interest of many researchers. In experiments, the transport characteristics of the nanochannel array are treated as a collective behavior of individual or single channel characteristics. To elucidate the ion transport phenomena, a single or isolated nanochannel is studied theoretically and is extrapolated to the nanochannel array. However, it has been demonstrated that the physics observed using a single or isolated nanochannel is quite different as compared to nanochannel arrays and nano slots. Furthermore, ion transport through the nanochannel array is shown as a function of interchannel spacing and communication among the channels. , The scalability of the nanoscale transport phenomena from a single channel to a large-scale system (i.e., nanochannel array and nanoporous membrane) is very challenging and is meagerly explored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the transport phenomena of a single or isolated nanochannel is of fundamental interest of many researchers. In experiments, the transport characteristics of the nanochannel array are treated as a collective behavior of individual or single channel characteristics. To elucidate the ion transport phenomena, a single or isolated nanochannel is studied theoretically and is extrapolated to the nanochannel array. However, it has been demonstrated that the physics observed using a single or isolated nanochannel is quite different as compared to nanochannel arrays and nano slots. Furthermore, ion transport through the nanochannel array is shown as a function of interchannel spacing and communication among the channels. , The scalability of the nanoscale transport phenomena from a single channel to a large-scale system (i.e., nanochannel array and nanoporous membrane) is very challenging and is meagerly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Communication between the channels is established through the access region effects, and overlapping of the diffusion zones due to the ion concentration polarization (ICP) phenomenon. , ICP is a nonequilibrium phenomenon indicating the depletion and enrichment of ions across the ion-selective devices under the action of an external electric field. ,, This ICP phenomenon results in nonlinear I – V characteristics (including ohmic and nonohmic regions). In literature, it is demonstrated that the independent diffusion transport through each pore can be achieved if the interpore distance is greater than 56 times of pore diameter .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study [36] analyzed transport phenomena described by Laplace equations (in particular, vapor diffusion in air within stagnant layers) in systems involving infinite regular arrays of "sources" (these can be, in particular, nanopore outlets in evaporation from porous materials). For infinite regular flat arrays with stagnant layers, the diffusion resistance was demonstrated to be well approximated by an in-series connection of the diffusion resistance of the stagnant layer and of an effective parallel connection of multiple nanopores.…”
Section: Infinite Arrays Of Nanopores and Nanoporous Materialsmentioning
confidence: 99%